The Effect Of Growtone As Growth Regulatory Substance On The Growth of Stock Steps Of Red Dragons Fruit (Hylocereus costaricensis Britton & Rose) - Rostian Nafery; Indrawani S; Fitria Harvika (Agrologia, 2022)
Dragon fruit plants can be propagated generatively by seeds and vegetatively by propagation of branch or stem cuttings. This study aims to examine the effect of Growtone's growth regulator on the growth of red dragon fruit stem cuttings. The treatment used Growtone with three concentration levels, namely 0 (without PGR as a control), 10 g ZPT/liter water, 15 g ZPT/liter water, and 20 g ZPT/liter water. The study was designed using a Randomized Block Design with six replications. Each experimental unit consisted of 10 plants. The plant growth responses measured were shoot growth time, number of shoots, shoot length, number of roots, root length, and root dry weight. The results of the study found that PGR Growtone had an effect on shoot length, root length, number of roots and root dry weight, but had no effect on shoot growth time and number of shoots. It is better to give Growtone ZPT with a concentration of 20 g/l water